Significant Others and Social Transformation: An Examination of the Ahmadiyah Conflict in Lombok - Mohamad Baihaqi; Firdaus AM; Ikmal Maulana; Ihfan Rahmawadi; Mia Rizki (Journal of Social Growth and Development Studies, 2025)
This research analyses the role of figures in the dynamics of internal Islamic conflict, particularly in the case of Ahmadiyah in Lombok. Using a qualitative method with a descriptive-analytical approach, data was collected through interviews with representatives of the Ahmadiyah congregation as well as secondary sources such as previous research, NGO reports, and mass media. The data obtained was categorised based on conflict patterns and mass psychology, then analysed using the framework of religious socialisation theory. The results show that important figures in both groups play a vital role as significant others in reducing conflict through three mechanisms: faith strengthening, internal Islamic dialogue, and faith modelling. This internal dialogue is key in finding common ground and managing differences in teachings within one religion. Thus, the presence of figures as mediators plays a strategic role in managing conflict, both in open form and at the doctrinal level.